2022
DOI: 10.1155/2022/4566851
|View full text |Cite
|
Sign up to set email alerts
|

The ROS/GRK2/HIF-1α/NLRP3 Pathway Mediates Pyroptosis of Fibroblast-Like Synoviocytes and the Regulation of Monomer Derivatives of Paeoniflorin

Abstract: Hypoxia is an important factor in the development of synovitis in rheumatoid arthritis (RA). The previous study of the research group found that monomeric derivatives of paeoniflorin (MDP) can alleviate joint inflammation in adjuvant-induced arthritis (AA) rats by inhibiting macrophage pyroptosis. This study revealed increased levels of hypoxia-inducible factor- (HIF-) 1α and N-terminal p30 fragment of GSDMD (GSDMD-N) in fibroblast-like synoviocytes (FLS) of RA patients and AA rats, while MDP significantly inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Intriguingly, according to recent studies, in addition to traditional IL-1β inhibitors, NLRP3 or P2X7R blockers also reduce the release of cartilage destruction factor IL-1β, and alleviate joint inflammation by controlling macrophage or FLS pyroptosis ( 151 153 ), which increases the potential therapeutic targets of RA.…”
Section: Role Of Pyroptosis In Autoimmune Diseasesmentioning
confidence: 99%
“…Intriguingly, according to recent studies, in addition to traditional IL-1β inhibitors, NLRP3 or P2X7R blockers also reduce the release of cartilage destruction factor IL-1β, and alleviate joint inflammation by controlling macrophage or FLS pyroptosis ( 151 153 ), which increases the potential therapeutic targets of RA.…”
Section: Role Of Pyroptosis In Autoimmune Diseasesmentioning
confidence: 99%
“…Recently, one study showed hypoxia excessed the level of ROS, which in turn caused the phosphorylation of G protein-coupled receptor kinase 2 (GRK2) serine 670 (S670), promoting the HIF-1α to initiate the NLRP3 inflammasome and consequent pyroptosis. 119 As a result, the hypoxia-activated ROS/GRK2/HIF-1α/NLRP3 axis may make RA inflammation worse.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Later, Wang et al 118 showed that IL‐6 activated the NLRP3 inflammasome through the axis of the cathepsin B (CTSB)/ATP pathway, and S100A9 (a calcium‐binding protein) may engage in this process. Recently, one study showed hypoxia excessed the level of ROS, which in turn caused the phosphorylation of G protein‐coupled receptor kinase 2 (GRK2) serine 670 (S670), promoting the HIF‐1α to initiate the NLRP3 inflammasome and consequent pyroptosis 119 . As a result, the hypoxia‐activated ROS/GRK2/HIF‐1α/NLRP3 axis may make RA inflammation worse.…”
Section: Pyroptosis In Inflammatory Bone Diseasesmentioning
confidence: 99%
See 2 more Smart Citations